The Phenomenon of Tax Aggressiveness is Associated with Capital Intensity, Inventory Intensity, profitability, and Leverage - Madani, Mayra Permata; Mujiyati, Mujiyati (Dinasti International Journal of Economics, Finance & Accounting, 2024)
Tax aggressiveness is an activity or reconstruction effort carried out with the aim of maximizing contributions to the company through tax management strategies. This study aims to analyze the effect of capital intensity, inventory intensity, profitability, and leverage on tax aggressiveness. The population studied was property and real estate companies listed on the Indonesia Stock Exchange from 2019 to 2022. Sampling using a purposive sampling method. The number of samples as many as 61 companies. Data collection techniques through documentation techniques using secondary data sources. Data analysis using multiple linear regression using statistical Application Program tools: Statistical Product and Service Solutions (SPSS). The results of this study showed that capital intensity, and profitability affect tax aggressiveness, while inventory intensity, and leverage did not affect tax aggressiveness.